Importance of Antithrombin Evaluation and Supplementation in Clinical Practice - Antonijevic, Nebojsa; Tasic, Ana; Jankovic, Zorana; Obradovic, Vanja; Djukic, Marija; Savic, Predrag; Aleksandric, Srdjan; Birovljev, Ljubica; Lekovic, Zaklina; Uscumlic, Ana; Matic, Dragan; Bukarica Gojkovic, Ljiljana; et al. (Medical Research, 2025)
Antithrombin (AT) is a key natural anticoagulant that primarily inhibits thrombin, factor Xa, and other procoagulant proteases, maintaining hemostatic balance. Deficiency in AT, whether inherited or acquired, significantly increases the risk of venous thromboembolism, obstetric complications  and  sporadically arterial thrombosis. Individuals with AT deficiency are 15 times more likely to develop thrombosis. Acquired deficiency is more common and may result from hypoproduction, excessive excretion or loss, increased consumption or dilution of AT. In conditions that cause an acquired antithrombin deficiency, especially in those patients hospitalized in intensive care units due to the high risk of acute venous thromboembolism, it is necessary to evaluate the level of antithrombin. Antithrombin is essential for the action of unfractioned heparin and low-molecular-weight heparin, meaning that deficiency can lead to resistance to these anticoagulants. AT deficiency is often detected when insufficient  anti-Xa levels are observed during heparin therapy and confirmation is achieved through direct AT level testing. Supplementation of AT is indicated for preventing and treating thrombotic events in patients with congenital or acquired AT deficiencies. The therapeutic approach includes three key strategies: treatment of acute thromboembolic events, short-term prophylaxis in high-risk situations and long-term prophylaxis, especially for patients with a history of thromboembolism due to AT deficiency. High levels of AT may cause a hemorrhagic tendency, particularly when used alongside heparin. Although AT has potential in treating sepsis-induced disseminated intravascular coagulation, most international guidelines still do not support its use for these indications. Given the pathogenic significance of AT in the development of thromboembolism and antithrombin-dependent anticoagulant resistance, monitoring its levels is crucial for adequate prophylaxis and treatment of thrombotic events.
Keywords: antitrombin; thromboembolism; heparin resistance; hemostasis